2019
DOI: 10.1039/c8ob02747a
|View full text |Cite
|
Sign up to set email alerts
|

DNA triplex-based fluorescence turn-on sensors for adenosine using a fluorescent molecular rotor 5-(3-methylbenzofuran-2-yl) deoxyuridine

Abstract: Fluorescence turn-on detection of adenosine based on microenvironmental and conformational changes of a fluorescent molecular rotor in the DNA triplex is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Similar working principles have been exploited to use environmentally sensitive probes to study base mismatches [140] and non‐canonical secondary structure of nucleic acids, [139a] including triplexes, [141] i‐motifs [142] or G‐quadruplexes (G4s). [ 130 , 143 ] G4s are non‐canonical nucleic acid structures that form in guanine‐rich regions of the genome, which are thought to have vital biological roles, acting as regulators of gene transcription, in replication and in telomere maintenance.…”
Section: Molecular Rotors For Biological Imagingmentioning
confidence: 99%
“…Similar working principles have been exploited to use environmentally sensitive probes to study base mismatches [140] and non‐canonical secondary structure of nucleic acids, [139a] including triplexes, [141] i‐motifs [142] or G‐quadruplexes (G4s). [ 130 , 143 ] G4s are non‐canonical nucleic acid structures that form in guanine‐rich regions of the genome, which are thought to have vital biological roles, acting as regulators of gene transcription, in replication and in telomere maintenance.…”
Section: Molecular Rotors For Biological Imagingmentioning
confidence: 99%
“…The use of non-denaturing PAGE is highly effective for both the qualitative and quantitative analyses of DNA triplexes but the use of radioactive material containing 32 P and/or other radionuclides requires expertise in handling, manufacture and the safe disposal of waste to protect against negative impact on the environment. Fluorescence-based [5] approaches provide potentially less expensive, greener methods for triplex DNA analysis. The use of a bifunctional triplex DNA sensor incorporating the 1,8-naphthilamide fluorophore and a naphthoquinoline motif was examined [6] and shown to be selective for triplex over duplex and single-stranded DNA, as judged by photoelectron transfer [7] (PET) assay.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that probes belonging to molecular rotor group can result in a large increase in their emission intensity upon binding with DNA molecules. Molecular rotors are characterized by an electron donor and electron acceptor moieties connected through a single bond. Such molecule upon photoexcitation undergoes very efficient torsional motion around that single bond and leads to the formation of a nonemissive twisted intramolecular charge transfer (TICT) state. Due to such process, the emission yield of molecular rotors is extremely low (<10 –3 ) in solvents with low viscosity, such as water, methanol, etc. However, upon association with biomolecules, the microviscosity around such molecular rotor increases and provides strong frictional forces toward the torsional motion in the excited state. , Hence, due to the binding, the nonradiative torsional process gets restricted and the emission quantum yield of such biomolecule-bound molecular rotor increases to a large extent.…”
Section: Introductionmentioning
confidence: 99%